Protracted fever after infliximab induction therapy in a patient with ulcerative colitis (clinical case) - E. Yu. Chashkova; E. V. Pak; L. R. Shedoeva; A. N. Gerasimenko (Acta Biomedica Scientifica, 2022)
Inflammatory bowel diseases (ulcerative colitis and Crohn’s disease) tend to increase in frequency and prevalence worldwide and lead to a significant reduction in quality of life with a complicated course. Intravenous administration of corticosteroids in acute severe ulcerative colitis is effective in 60–70 % of cases. Rescue therapy for patients with steroid‐refractory and steroid-dependence attacks is effective for reducing colectomy or colproctectomy and improves long-term treatment outcomes. Despite the proven efficacy of infliximab, limitations to the use of monoclonal antibodies are adverse reactions to the administration of genetically engineered biologic therapy (GEBT), both well-known and studied, and rare.The aim of the study. To analyze a case of an extremely rare and paradoxical incurable hyperergic reaction that occurred after using genetically engineered biological therapy with tumor necrosis factor alpha blockers in a patient suffering from ulcerative colitis.Materials and methods. We carried out the search in the PubMed, Embase, Scopus and Medline databases until November 1, 2022 using the following keywords: inflammatory bowel disease, ulcerative colitis (UC), anti-tumor necrosis factor α (antiTNFα), infliximab, fever, adverse events. In the scientific electronic library eLIBRARY, a search was made for Russian-language publications using similar queries in Russian. We analyzed the patient’s medical records from 03.06.2013 up to the present day; the patient signed an informed consent for the publication and discussion of the presented data.Conclusion. The widespread use of GEBT in the treatment of autoimmune and autoinflammatory diseases leads to the accumulation of both positive and negative experience of clinicians in real clinical practice. The officially described adverse events in the appointment of any drug suggest options for their prevention and treatment. Atypical manifestations or casuistic cases must be systematized for further fundamental pathophysiological studies.